“How can I help you?”: communication skills of front desk officers - Wan Mahmood, Wan Mas Athirah; Ariffin, Adlina (2018)
This paper describes a study which investigated the communication skills of front desk officers at a Malaysian higher learning institution. Using verbal recordings, interviews and researcher’s observation and annotation, data was collected from conversation between administrative staff and international students in order to indentify the communication strategies used by the staff and the effectiveness of those strategies. The findings revealed that fillers, asking for confirmation and asking for clarification were the three most frequent communication strategies used. In general, the students were very satisfied with the communication skills of the officers due to their informativeness, courtesy and politeness. The findings from this study shall provide beneficial implications in enhancing communication quality and skills of front liners and service providers at higher education institutions.